1995
DOI: 10.1007/bf00298540
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology and complications of chronic pilonidal sinus treated with excision and primary suture

Abstract: Two prospective studies were undertaken to examine the role of bacteria in the outcome after excision and primary suture for chronic pilonidal sinus disease. In the first study 52 consecutive patients were given cloxacillin as prophylaxis. In a second randomised study 51 patients were given 2 g cefoxitin intravenously (n = 25) or no prophylaxis (n = 26). From 49 out of 98 patients (50%) no microorganisms were isolated from sinuses preoperatively. Wound complications were observed postoperatively in 61% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 11 publications
4
55
1
8
Order By: Relevance
“…Literature has documented a recurrence rate of 0-3% for Limberg flap against a significantly high recurrence of 7-42% for primary closure. 26,[33][34][35][36][37][38] Our study also three recurrences in primary closure and nil in case of Limberg flap group and nil in 3 rd group where healing was by secondary intention. Our results also support those patients in primary closure group walked freely without significant pain after a relatively longer period than patients treated with flaps because of the tension created by the primary suture technique.…”
supporting
confidence: 63%
“…Literature has documented a recurrence rate of 0-3% for Limberg flap against a significantly high recurrence of 7-42% for primary closure. 26,[33][34][35][36][37][38] Our study also three recurrences in primary closure and nil in case of Limberg flap group and nil in 3 rd group where healing was by secondary intention. Our results also support those patients in primary closure group walked freely without significant pain after a relatively longer period than patients treated with flaps because of the tension created by the primary suture technique.…”
supporting
confidence: 63%
“…So, looking that way one expects flap procedures to combat the disease recurrence better than excision with simple closure, keeping in view extensive dissection of the sinus tracts and the shallower cleft that flap procedures provide. Literature has documented a recurrence rate of 0-3% [2][3][4][5][6] for Limberg flap against a significantly high recurrence of 7-42% [7,8] for primary closure. Outcome of our study in terms of recurrence of the sinus is the same as reported by other studies, namely, three recurrences for the primary closure group against zero recurrence of the Limberg flap group.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperatif değişen sürelerde verilen antibiyotiklerin yararı tartışmalı olmakla beraber profilaktik antibiyotiklerin yara komplikasyonlarını veya rekürensi azaltmadığı, iyileşmeyi hızlandırmadığı, genel olarak bakıldığında bu amaçlarla kullanılan antibiyotiklerin yara infeksiyon riskini azaltma konusunda yardımcı olmadığı belirlenmiştir (14) . Apse gelişen olgularda lokal anestezi ile apsenin drene edilmesi tek çözümdür.…”
Section: Tedaviunclassified